Bioethics regulations in Turkey - Aydin, Emanuel (Journal of medical ethics, 1999)
Although modern technical and scientific developments in medicine are followed closely in Turkey, it cannot be claimed that the same is true in the field of bioethics. Yet, more and more attention is now being paid to bioethics and ethics training in health sciences. In addition, there are also legal regulations in bioethics, some of which are not so new. The objective of these regulations is to provide technical and administrative control. Ethical concerns are rather few. What attracts our attention most in these regulations is the presence of the idea of "consent".